Taller de oratoria para mejorar las habilidades comunicativas lingüísticas en los estudiantes del 5to y 6to grado de primaria en la I.E José Carlos Mariátegui - Mendoza Hernández, Nórvil (2012)
The purpose of this "investigation was to perform a public speaking workshop to improve communication skills in linguistic and non-language students in fifth and sixth grade of primary edycation of School Experimental José Carlos Mariátegui Rioja -2010. ·ro meet the objectives, was based on studies of the history of research, anthropological theories, linguistic, Marxist communication, programming neurolinguistic, emotional intelligence and multiple intelligences in which conceptualized the study variables. Sych theoretical framework allowed to raise the following hypothesis: The Public Speaking Workshop will significantly improve communication skills in l~ngi,J~ge ~nq non-í~nguage students in fifth and sixth grades of primary education of School Experimental José Carlos Mariátegui - Rioja. lhe research design was pretest ano post test with one gro\Jp, which belongs to the preexperimental design. The sample consisted of 15 students in fifth and sixth grades of primary education, with the development of six workshops with the use of techniques and Discussion Panel. When contrasted the hypothesis, we obtained a = -33.79 T-calculated higher than Ttabulated = -1.761, with a= 0.05, concluding that the "Workshop on Public Speaking" significantly improved l~ngi,Jage commi,Jnic~tion skills ~nd st\Jdentsi l~ngu~ge prlmary education institution Experimental Education José Carlos Mariátegui - Rioja.